anonymous
  • anonymous
If tan A - tan B = x and cot B - cot A =Y , pt COT (a-b) = 1/X + 1/Y
Mathematics
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
anonymous
  • anonymous
sin(A-B)/ cosA*cosB =1/x from Tan A - tan B=x
anonymous
  • anonymous
okay !

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
then ?
anonymous
  • anonymous
and sin(A-B)/ sinA* SinB=y from cotB- cotA =y sin(A-B)/ cosA*cosB =x from Tan A - tan B=x tanA*tanB= x/y
anonymous
  • anonymous
@akash123 sin(A-B)/ cosA*cosB =x from Tan A - tan B=x
anonymous
  • anonymous
cot(A-B) = [ cot A* cot B+1] / ( cot B - cot A)
anonymous
  • anonymous
yes...thanks...I have corrected it later
anonymous
  • anonymous
sin(A-B)/ sinA* SinB=y from cotB- cotA =y sin(A-B)/ cosA*cosB =x from Tan A - tan B=x divide 2nd by 1st then u'll get tanA*tanB= x/y
anonymous
  • anonymous
yes i understood that !
anonymous
  • anonymous
now use the identity cot(A-B) = [ cot A* cot B+1] / ( cot B - cot A) and substitute the value of cot A* cot B and (cot B- cot A) then u'll get the answer
anonymous
  • anonymous
another way @sauravshakya write the reciprocal f 1st and 2nd equation and add both then simplify it.
anonymous
  • anonymous
Yep... I would go with that....
anonymous
  • anonymous
okay got it :) thank you !
anonymous
  • anonymous
:)

Looking for something else?

Not the answer you are looking for? Search for more explanations.